The Role of the Dutch East Indies Government in Building Pontianak City Center - Firmansyah, Andang; Mirzachaerulsyah, Edwin (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
This research aims to discuss the role of the Dutch East Indies Government in developing the Tanah Seribu area which is now known as Pontianak Kota District. Pontianak Kota District is currently the center of Pontianak City because of the infrastructure that the Dutch built. Dutch heritage buildings contain history that people have begun to forget due to the times. This research method uses a historical method which consists of five stages, namely topic selection, source collection, verification, interpretation and writing. The results of this research reveal the history of buildings left by the Indies government as evidence that the Dutch played a role in forming the center of Pontianak City. Several Dutch heritage buildings were very useful for the Pontianak City Government in the early days of Indonesian independence. Indonesia's unstable conditions do not allow the government to build facilities, so the City Government utilizes Dutch heritage buildings. Some of the buildings are still in use today, and have even become Pontianak City Cultural Heritage because they contain historical significance. This determination shows that the Dutch East Indies Government also left good things for Indonesia.